Evaluating the Central and Eastern European Countries in Terms of Implementing the Industry 4.0 Technologies in Small and Medium-Sized Enterprises - Magdalena TUTAK (Communications of International Proceedings, 2021)
The implementation of Industry 4.0 technologies is increasingly important for the global economy. This particularly concerns small and medium-sized enterprises (SMEs) in individual countries, including the countries of Central and Eastern Europe. The aim of this article was to assess the implementation level of these technologies in individual Central and Eastern Europe countries (11 EU countries). In order to achieve this goal, this level was assessed using 9 selected determinants (indicators) characterizing the most crucial areas concerning digital transformation. The research was conducted for 11 countries in the region, with reference to the SME sector, i.e., companies of great importance for the economic development of these countries. The VIKOR method was used for the research, and the Shanon's Entropy method was used to determine the weights of the determinants. The results show a great diversity in the implementation level of Industry 4.0 technologies in SMEs in the Central and Eastern Europe countries. Four classes of the level of progress in implementing these technologies in the Central and Eastern Europe countries were distinguished. The high level was found for the Czech Republic and Slovakia, and the low level for Hungary and Romania. The analysis of the influence of GDP of individual countries on the implementation level of Industry 4.0 technologies was also performed.
Keywords: Digital Transformation; Industry 4.0 Technologies; Small and Medium-Sized Enterprises; Central and Eastern Europe; VIKOR Method.